Pengaruh Persepsi Kemudahan Penggunaan, Efektivitas, dan Risiko Terhadap Minat Bertransaksi Menggunakan Financial Technology (POSPAY) pada Masyarakat Kabupaten Pemalang - Naelan Nur Fariz; Ira Setiawati; Meiriyanti, Rita Meiriyanti (Universitas PGRI Semarang, 2024)
This research aims to determine the influence of perceived ease of use, effectiveness and risk on interest in transactions using POSPAY financial technology among the people of Pemalang Regency. This research uses quantitative methods, where data collection techniques are carried out using questionnaires distributed online, This research processes data using the IBM SPSS 26 tool. The research results show that the test results show that the variables Perception of Ease of Use, Effectiveness and Risk are proven to have a positive and significant influence on interest in transactions using POSPAY financial technology in the people of Pemalang Regency